Assessment of Service Quality in Community Health Center Using Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) - Endang Pudji Widjajati; Mega Cattleya Prameswari Anissa Islami (Future Science, 2022)
The spread of the virus makes the presence of health facilities very important. The public health center must provide health services to improve the health status of the community. Its operation, there are several complaints about the existing facilities at the Kedamean Gresik Health Center, so it is necessary to research the quality of service in that place. The purpose of this study is to analyze the value of service satisfaction and determine the attributes that need to be evaluated to improve services at the public health center. Data was collected by distributing questionnaires to 100 respondents who were patients at the public health center. The data obtained were processed using the Customer Satisfaction Index (CSI) and Importance-Performance Analysis (IPA) methods. The results showed a customer satisfaction index of 70.8% which means that customers at the Kedamean Gresik Health Center are satisfied with the services provided, but it is necessary to make improvements in certain attributes. Based on the results of the analysis of attributes that need to be improved, they consist of A3, B2, B3, C2, C3, and E1 in quadrant B, and service attributes consisting of A2, A4, C1, and D1 in quadrant A.